Here's the question you clicked on:
_TylerTaughtMe
Simplify −(6p + 12) 6p − 12 6p + 12 −6p + 12 −6p − 12
when you have a minus sign next to parentheses like that its the same thing as this: \[(-1)(6p + 12)\]
and now you just have to distribute that negative one to each term inside the parentheses
I Dont Get It ...
which part? changing the minus sign to negative one or distributing?
Parenthesis means nothing when they are surrounding a number, or a group of numbers, when not used in a longer problem. For example, -(6) is just -6. Or -(a+b) is still -a+b.
-(a + b) does not equal -a + b, you must distribute the negative sign to each term in the parentheses
Right, sorry. You corrected that for me, haha. Saw that wrong.
Simplify −(6p + 12) =>(-6p - 12) ◄ Ans 6p − 12 ← same 6p + 12 ← same −6p + 12 => -(6p + 12) => (-6p - 12) ◄ Ans −6p − 12 =>-(6p -12) => (-6p + 12) ◄ Ans
(-1x 6p) + (-1x12) =-6p -12. See how that works?